DEVELOPMENT OF 3D DYNAMITE BOX VIDEO MEDIA DEVELOPMENT OF GLOBAL PERSPECTIVE COURSES BASED ON CASE METHOD IN PGSD STUDY PROGRAM - Husna Parluhutan Tambunan; Yusra Nasution; Rahmilawati Ritonga; Dwi Yulia Annisa; Cepty Yuria Pratam (RADJA PUBLIKA, 2022)
This study aims to determine the development, feasibility and practicality of 3-dimensional learning video media for the case method-based global perspective course in the PGSD study program. This type of research is research and development using the ADDIE model. The instruments used are material expert validation sheets, media experts and student response questionnaires. The results of research related to feasibility show that at this stage the researcher evaluates the media that has been developed based on the results of the media feasibility assessment by material experts, media experts, and lecturers. 90% ( material), 95.38% (media), 91.64% (practical) . Based on the results of the validation of Animaker-based animation learning media, it is in the